The research environment of critical care in three Asian countries: A cross-sectional questionnaire survey - Kotani, Yuki; Na, Sungwon; Phua, Jason; Shime, Nobuaki; Kawasaki, Tatsuya; Yasuda, Hideto; Jun, Jong Hun; Kawaguchi, Atsushi (Frontiers in Medicine, 2022)
Although inadequate research support for intensivists can be one major reason of the poor research productivity, no study has investigated the current research environment in critical care medicine in Asia. The objective of this study was to describe Asian academia in critical care from the research environment perspective. We conducted a cross-sectional questionnaire survey targeting all physician members of the Societies of Intensive/Critical Care Medicine in Japan, South Korea, and Singapore. We collected the characteristics of the participants and their affiliated institutions and the research environment. The outcome was the number of peer-reviewed publications. Multivariable logistic regression analyses examined the association between the outcome and the following five research environmental factors (i.e., country of the respondents, availability of secured time for research activities or research supporting staff for the hospital, practice at a university-affiliated hospital, and years of clinical practice of 10 years or longer). Four hundred ninety responded (overall response rate: 5.6%) to the survey between June 2019 and January 2020. Fifty-five percent worked for a university-affiliated hospital, while 35% worked for a community hospital. Twenty-four percent had secured time for research within their full-time work hours. The multivariable logistic model found that a secured time for the research activities [odds ratio (OR): 2.77; 95% confidence interval (CI), 1.46–5.24], practicing at a university-affiliated hospital (OR: 2.61; 95% CI, 1.19–5.74), having clinical experience of 10 years or longer (OR:11.2; 95%CI, 1.41–88.5), and working in South Korea (OR: 2.18; 95% CI, 1.09–4.34, Reference: Japan) were significantly associated with higher research productivity. Intensivists in the three countries had limited support for their research work. Dedicated time for research was positively associated with the number of research publications.